2012
DOI: 10.1371/journal.pone.0035778
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Anaphylaxis Management Guidelines: A Register-Based Study

Abstract: BackgroundAnaphylaxis management guidelines recommend the use of intramuscular adrenaline in severe reactions, complemented by antihistamines and corticoids; secondary prevention includes allergen avoidance and provision of self-applicable first aid drugs. Gaps between recommendations and their implementation have been reported, but only in confined settings. Hence, we analysed nation-wide data on the management of anaphylaxis, evaluating the implementation of guidelines.MethodsWithin the anaphylaxis registry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 24 publications
4
45
0
2
Order By: Relevance
“…[16] That study, performed using the transnational anaphylaxis registry of Germany, Austria, and Switzerland, confirmed major discrepancies in treatment and follow-up and recommended a revised approach to management, including training and education. No data exist for the US.…”
Section: Introductionmentioning
confidence: 88%
“…[16] That study, performed using the transnational anaphylaxis registry of Germany, Austria, and Switzerland, confirmed major discrepancies in treatment and follow-up and recommended a revised approach to management, including training and education. No data exist for the US.…”
Section: Introductionmentioning
confidence: 88%
“…Data from several cohort studies illustrate the extent of under-treatment of anaphylaxis and the low rate of adrenaline use (12,15,(39)(40)(41), with most cases of anaphylaxis that require hospitalization not receiving an AAI on discharge. Adrenaline is much less commonly used than antihistamines and corticosteroids in treating anaphylaxis despite both antihistamines (42) and corticosteroids (43,44) having an onset of action that is delayed and too late to prevent respiratory and/ or cardiovascular arrest, which can occur within minutes (23).…”
Section: Limited Awareness Of the Treatment Of Anaphylaxis By Health mentioning
confidence: 99%
“…From the anaphylaxis registry that includes 83 centres in Germany, Austria and Switzerland, validated data from 58 of the centres and consisting of 2114 consecutive cases (2006-2010) of severe anaphylaxis were recently analysed (41), to establish the degree of compliance with treatment recommendations. This study revealed that adrenaline was given to only 13.8% of the patients, with just 3.9% receiving im injection (Fig.…”
Section: Limited Awareness Of the Treatment Of Anaphylaxis By Health mentioning
confidence: 99%
“…Intravenous adrenaline is an option in patients with severe hypotension or cardiac arrest unresponsive to intramuscular doses of adrenaline and fluid resuscitation 1. Despite these therapeutic benefits of adrenaline and the recommendations for its use, adrenaline injection rates remain low in many ERs37, 38 (Fig. 5).…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
“…Drugs used for emergency treatment of anaphylaxis, according to age 37. The dashed lines indicate the proportion of patients who received only inhalation (adrenaline) or oral (antihistamine or corticoid) treatment.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%